Power Consumption Based Efficient Routing With Mobile Collector in Wireless Sensor Networks - Santhi, S.G; Nathiya, R (International Journal of Computer Sciences and Engineering, 2014)
Energy consumption is a primary concern in the Wireless Sensor Network. Which leads to pursue the maximum energy saving at sensor nodes, where a relay is used to transfer the data packet. This leads to the increase in the data gathering latency due to low moving velocity of the mobile collector. In this paper we study the tradeoff between energy saving and data gathering latency in mobile data gathering by exploring a balance between the relay hop count of local data aggregation and the moving tour length of the mobile collector. In this we propose a polling based mobile gathering approach, which leads to optimization problem named bounded relay hop mobile data gathering (BHR - MDG). A subset of sensors are used for the polling points. Thus these are the two efficient algorithms for selecting polling points among sensors.